KEMAMPUAN EKSTRAK ETANOL DAUN KELOR (Moringa oliefera) DALAM MENGHAMBAT PEMBENTUKAN BIOFILM Escherichia coli: The Inhibitory Activity of Kelor (Moringa oliefera) Leaves Ethanolic Extract on Escherichia Coli Biofilm Formation - Suryani Hutomo; Ni Wayan Rosa Anggreni; Ceny Gloria Larope; Ni Wayan Maitri Puspadi Trismalinda; Ni Komang Ayulia Sari; Christiane Marlene Sooai (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Escherichia coli is a Gram-negative bacterium which is the main etiologic of urinary tract infection. This species adheres on host tissue and forms biofilm as one of its virulence factors. The increasing cases of antibiotics resistance towards this bacterium causes to develop methods to control E. coli biofilm formation. Kelor (Moringa oliefera) leaves have known to be an antibiotic. The aim of this study is to analyze the ability of kelor leaves extract to inhibit E. coli adherence. Kelor leaves were extracted with the maceration method. The susceptibility of E. coli to this extract was examined by a minimum inhibitory concentration (MIC) test using the broth microdilution method. A bacterial adherence assay was performed by similar methods of the MIC assay. The MIC value for the kelor leaves extract was at a concentration of 5,000 μg/ml. Moreover, this extract inhibited E. coli adherence starting at a concentration of 125 μg/ml and reached a maximum at a concentration of 2,000 μg/ml. Statistical analysis using One-way Anova demonstrated a significant difference of E. coli adherence following stimulation with kelor leaves extract (p = 0.000). In conclusion, kelor leaves extract can inhibit E. coli biofilm formation. ABSTRAK Escherichia coli merupakan bakteri Gram negatif penyebab utama infeksi saluran kemih. Kemampuan bakteri ini untuk melekat pada host dan membentuk biofilm merupakan salah satu faktor virulensinya. Adanya resistensi antibiotik pada bakteri ini menyebabkan perlunya dikembangkan metode untuk mengendalikan pembentukan biofilmnya. Daun kelor (Moringa oliefera) diketahui memiliki sifat antibakteri. Tujuan penelitian ini adalah untuk menganalisa kemampuan ekstrak etanol daun kelor dalam menghambat perlekatan E. coli. Pembuatan ekstrak menggunakan metode maserasi. Konsentrasi hambat minimal (MIC) ditentukan dengan metode broth microdilution. Uji anti perlekatan dilakukan dengan metode yang sama. MIC ekstrak daun kelor terdapat pada konsentrasi 5000 µg/ml. Penghambatan perlekatan dimulai pada konsentrasi 125 µg/ml dan mencapai maksimum pada konsentrasi 2000 µg/ml. Analisis statistik menggunakan One-way Anova menunjukkan perbedaan yang bermakna dari perlekatan E. coli setelah dipapar ekstrak daun kelor (p = 0,000). Kesimpulan penelitian ini bahwa ekstrak etanol daun kelor dapat menghambat pembentukan biofilm E. coli.